Functional characterization of at-level hypersensitivity in patients with spinal cord injury - Vogel, Carola; Rukwied, Roman; Schley, Marcus; Schmelz, Martin (The journal of pain, 2017)
At-level and above-level hypersensitivity was assessed in patients with chronic complete thoracic spinal cord injury (SCI). Patients were classified using somatosensory mapping (brush, cold, pinprick) and assigned into 2 groups (ie, patients with at-level hypersensitivity [SCIHs, n = 8] and without at-level hypersensitivity [SCINHs, n = 7]). Gender and age-matched healthy subjects served as controls. Quantitative sensory testing (QST), electrically- and histamine-induced pain and itch, laser Doppler imaging, and laser-evoked potentials (LEP) were recorded at-level and above-level in SCI-patients. Six of 8 SCIHs, but 0 of 7 SCINHs patients suffered from neuropathic below-level pain. Clinical sensory mapping revealed spreading of hypersensitivity to more cranial areas (above-level) in 3 SCIHs. Cold pain threshold measures confirmed clinical hypersensitivity at-level in SCIHs. At-level and above-level hypersensitivity to electrical stimulation did not differ significantly between SCIHs and SCINHs. Mechanical allodynia, cold, and pin-prick hypersensitivity did not relate to impaired sensory function (QST), axon reflex flare, or LEPs. Clinically assessed at-level hypersensitivity was linked to below-level neuropathic pain, suggesting neuronal hyperexcitability contributes to the development of neuropathic pain. However, electrically evoked pain was not significantly different between SCI patients. Thus, SCI-induced enhanced excitability of nociceptive processing does not necessarily lead to neuropathic pain. QST and LEP revealed no crucial role of deafferentation for hypersensitivity development after SCI. Perspective. At-level hypersensitivity after complete thoracic SCI is associated with neuropathic below-level pain if evoked by clinical sensory stimuli. QST, LEP, and electrically-induced axon reflex flare sizes did not indicate somatosensory deafferentation in SCIHs.